Pengaruh Pemahaman Standar Akuntansi Pemerintah dan Pemanfaatan Sistem Informasi Akuntansi Terhadap Kualitas Laporan keuangan di Kantor Sekretariat Daerah Kota Palembang - Indah Pitaloka; M. Titan Terzaqh (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to ascertain how the Palembang City Regional Secretariat Office's government financial reports are affected by the usage of accounting information systems (SIA) and a comprehension of government accounting standards (SAP). This kind of research combines quantitative techniques with the hypothetico-deductive process. In order to gather primary data for this study, questionnaires were sent to the Palembang City Regional Secretariat office's planning and budget department. In order to obtain a total of 40 respondents, the sample was determined using a purposive sampling technique with the criteria of employees working in the planning and finance section of the regional secretariat of the city of Palembang, specifically serving as Head of Division, Head of Planning, Reporting, Treasurer, and Finance Staff. The Statistical Package For The Social Science (SPSS) 22.0 for Windows is used by the data analysis tool. The findings of this study suggest that the quality of financial reports is significantly impacted by both the use of accounting information systems and knowledge of government accounting standards.